Evaluation of the effectiveness of basic cardiopulmonary resuscitation training on willingness to perform CPR among high school students - Mojtaba Hamednia; Ameneh Yaghoobzadeh; Rahmatollah Moradzadeh; Somaye Sayahi (BMC Cardiovascular Disorders)
Abstract Introduction Given the high prevalence of cardiovascular diseases and sudden cardiac arrest, training in basic cardiopulmonary resuscitation (CPR) skills, especially during adolescence, can play a crucial role in increasing awareness and preparedness in individuals facing emergency situations. The present study aimed to evaluate the effectiveness of basic CPR training on the willingness to perform it among high school students. Methods This study is an educational intervention. A simple random sampling method was employed to select 100 individuals in each of the intervention and control groups from four governmental boys’ high schools. The data collection tool was a questionnaire assessing the willingness to learn and perform CPR, which has been validated and shown to be reliable. The educational intervention consisted of three sessions covering the history, practical techniques, and use of AED devices, utilizing diverse educational methods such as PowerPoint presentations, educational videos, and hands-on practice. Data were analyzed using SPSS version 26 and appropriate statistical tests. Results The results indicated that basic CPR training significantly impacted students’ willingness to learn, perform CPR, and related knowledge. The changes in willingness to learn (p = 0.001), willingness to perform CPR (p = 0.001), and knowledge of CPR (p = 0.001) were significantly greater in the intervention group compared to the control group. These findings demonstrate the positive effect of CPR training on increasing willingness to learn, perform, and knowledge of CPR. Conclusion The results of this study showed that basic CPR training has a positive and significant impact on increasing willingness to learn, willingness to perform CPR, and related knowledge among students. The intervention group displayed significant changes in these variables after receiving training. Therefore, CPR-related education can be considered an effective tool for enhancing awareness and preparedness for performing these life-saving actions. Clinical trial number N/A.